Rape Kits in Context: A semi-systematic literature review of international rape kit best practices and their implications for the South African setting - Bobbert, Jessica Frances (Department of Public Law, 2022)
Sexual violence is a pervasive problem in South Africa. Although we have pioneered a range of specialised post-rape structures and services over the last two decades, access to and availability of such services is varied, and the systems are plagued by inadequate training, weak intersectoral collaboration and a lack of resources, which result in significant provincial discrepancies (Jewkes et al., 2009; Machisa et al., 2017; Vetten et al., 2008). Evidence suggests that Sexual Assault Evidence Collection Kits (SAECKs) is one area that demands urgent attention. The current backlog in analysing SAECKs is estimated to be at over 100 000 DNA samples (Waterworth, 2020). As local research on SAECKs is limited both in quantity and scope, this study undertook a semi-systematic literature review of published articles that address rape kits and international best practices to identify evidence-based recommendations for SAECK policy and future research. From a total of 206 sources, 31 were eligible for inclusion in the review with all but one article presenting research conducted in the United States, predominantly focusing on the national rape kit backlogs. The literature shows that ineffective use of SAECKS in South Africa may not be the result of a lack of specialised services but rather the poor implementation of related policy. Recommendations for best practices must address these challenges while also accounting for the context-specific factors that may impact the uptake and implementation of rape kit policy, such as the availability of resources, accountability mechanisms and the prioritisation of sexual assault cases. The key recommendation argues for expanding and improving existing provisions in respect of SAECKs in South Africa and identifies realistic and strategic measures for addressing their ineffective use.